Phenolics composition and contents, as the key quality parameters of table grapes, may be influenced obviously and differently in response to short-term high temperature. (September 2021) - Zhang, Lingling; Li, Xingyan; Pang, Yaxing; Cai, Xinyu; Lu, Jun; Ren, Xueyan; Kong, Qingjun
Abstract: Although the grape surface appears to be normal under high temperature during the selling period, the nutritional quality of grape might be greatly affected. Phenolics content and composition are key indicators reflective of grape's nutritional quality. Herein, the paper investigated effects of short-term high temperature (40 °C; 2 h) on grape phenolics from five table grape varieties to evaluate grape quality. Twenty-three phenolics were identified and quantified through UHPLC-ESI-qTOF-MS 2 and UHPLC-QQQ-MS 2, respectively. The results observed that short-term high temperature significantly reduced flavonoids in European and American varieties. In Eurasian varieties, high temperature induced the accumulation of stilbenes and flavonols compounds while lowered other compounds. Myricetin 4′-methylether-3 -O- rhamnoside, a differential metabolite responding to high temperature in all table grapes was screened. Combining with the analysis of molecular level, high temperature down-regulated the phenolics biosynthesis-related genes involved in phenolics metabolic pathways (flavonols, stilbenes, anthocyanins and flavan-3-ols metabolic pathways) in grapes except Muscat de Hambourg grapes, such as the expression of VvUFGT, VvANR, VvLAR, VvFLS, VvSTS, VvF3′5′H and VvAOMT. Our findings suggest that short-term high temperature during the selling period is not conducive to consumer expectations, due to the partial loss of grape nutrition quality. Highlights: The response of different grape varieties to short-term high temperature stress is different. There is no abnormality on the grape surface but nutritional value has deteriorated in treatment groups. Explaining the change of grape phenolics through molecular level. The change of grape phenolics metabolism pathway can reveal the change of grape nutritional value.